Contextual Theological Review Of The Meaning Of Tamo Cake In The Tulude Tradition And Its Impact On Faith Growth In The GMIM Batu Karang Bualo Congregation, Bunaken Region - Jefry Kalalo; Christoblless Evryanto Sawotong (Green Publisher Indonesia, 2024)
This article presents a contextual theological review regarding the meaning of Tamo Cake in the Tulude Tradition and its impact on the growth of faith in the GMIM Batu Karang Bualo Congregation, Bunaken Region. Tamo cake, which is made from sticky rice, sugar, coconut and coconut milk, not only serves as a dish in Tulude ceremonies, but also holds the noble values that are the cultural heritage of the people of North Nusa. This research aims to maintain the Tulude Tradition, which includes Tamo Cake, as a means of increasing the growth of Christian faith. Using qualitative methods and in-depth analysis, this article links the Tamo Cake to Christian values, highlighting how the meaning of this cake can strengthen social bonds and increase the spiritual awareness of the congregation. Tamo cake is a symbol of unity and harmony, which is able to penetrate differences in a pluralistic society. The research results show that Tamo Cake in the Tulude Tradition not only functions as ritual food, but also as a medium for communicating theological and educational values that are relevant to the context of congregational life in relation to Contextual Theology and the cultivation of Christian values for Christian Religious Education. Thus, this tradition has great potential in building faith and harmony between religious communities. This article ends with a conclusion that emphasizes the importance of maintaining traditions as part of a community's cultural identity and spirituality.